Beyond the Simulation Laboratory: A Realist Synthesis Review of Clinical Outcomes of Simulation-Based Mastery Learning. (November 2015) - Griswold-Theodorson, Sharon; Ponnuru, Srikala; Dong, Chaoyan; Szyld, Demian; Reed, Trent; McGaghie, William C.
Abstract : Purpose: Translational educational outcomes have been defined as starting in simulation laboratories (T1) and moving downstream to improved patient care practices (T2), patient outcomes (T3), and cost/other value outcomes (T4). The authors conducted a realist synthesis review of the literature to evaluate the translational effect of simulation-based mastery learning (SBML) principles beyond the laboratory. They also sought to address future directions in SBML to improve patient care processes and outcomes and, thus, the quality of health care delivery. Method: The authors searched multiple databases for simulation-based medical education (SBME) studies published through April 2013. They screened articles using the PICO method—population (P), intervention (I), control (C), outcome (O)—to answer the research question: For (P) any health care providers, does the (I) implementation of SBML training, compared with (C) other training methodologies or no extra training, result in (O) a change in patient care practices or T2–T4 outcomes? Studies implementing SBME interventions with training methodologies that met all SBML principles and reporting T2–T4 outcomes were identified. Results: The 14 included studies used pre/post or cohort study designs; the majority were limited to individual performance and procedural competency. They reported improvement after SBML training in procedure performance, task success, patient discomfort, procedure time, complication rates, or T4 impacts (e.g., cost reduction). Conclusions: Findings suggest health professions education conducted using SBML methodology can improve patient care processes and outcomes. Further research is needed to understand the translational impact of SBML for nontechnical skills, including teamwork, and skill retention.